PENGARUH PENGGUNAAN MEDIA PUZZLE GAMBAR BERWARNA DALAM PEMBELAJARAN KOOPERATIF TIPE NHT TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI SMAN 1 KOTO XI TARUSAN - Ristiono Ristiono; Ernie Novriyanti; Lamia Trisni Yuda (Ta'dib, 2012)
Learning achievement on Biology subject of the eleventh grade students of SMAN I Koto XI Tarusan was still low due to teachers’ dominance in learning process, and students’ lack of interest toward instructional media used by their teachers. The use colorful puzzled picture for instructional media was expected to be able to stimulate learning activity and arouse students’ motivation and, in turns, improve students’ learning achievement. This research was therefore aimed at figuring out the effect of using colorful puzzle for instructional media in cooperative learning, especially  Number Head Together type, upon Learning achievement on Biology subject of the eleventh grade students of SMAN I Koto XI Tarusan in the academic year of 2010/2011 academic year. This research employed quasi experimental with Static Group Comparison which compares the use colorful puzzled pictures for instructional media and colorful pictures only. The population was all eleventh grade students of SMAN I Koto XI Tarusan in the academic year of 2010/2011 academic year. Sampling technique was purposive where XI IPA5 and XI IPA6  were chosen. Data from final test was in the form of objective test consisting 40 items were analyzed to test the hypothesis using t-test where if  t calculated > t table, then the hypothesis was accepted.Kata kunci: puzzle, gambar berwarna,  NHT, hasil belajar, biologi